Hide and Seek - John Polson; Irving, Amy.; Dakota Fanning; Dylan Baker; Elisabeth Shue; Famke Janssen; Melissa Leo; Robert De Niro (USA Twentieth Century-Fox Film Corporation, 2005)
Hide and Seek revolves around a widower (Robert DeNiro) and his daughter (Dakota Fanning). They move to upstate and Emily (Fanning) soon creates an imaginary friend named Charlie...but this act takes an unexpected and terrifying turn, where her father and doctor (Famke Janssen) start to worry about Emily's gruesome habits.
As a widower tries to piece together his life in the wake of his wife's suicide, his daughter finds solace -- at first -- in her imaginary friend.
Ari Schlossberg
Language: English
Subtitle: Turkish
Keywords: Drama; Horror; Thriller